Correlation Between Partathyroid Hormone And Left Ventricular Function In Chronic Kindey Disease Patients - R. KUMARESAN; P.GIRI (International Journal of Pharma and Bio Sciences, 2012)
Cardiovascular risk factors are a significant burden in chronic kidney disease (CKD). Abnormalities of left ventricle (LV) structure and function are present in 70-80% of patients with CKD and more than half of them die of cardiovascular diseases. In this study we aimed to correlate, parathyroid hormone (PTH) levels with left ventricular hypertrophy (LVH) and LV ejection fraction by 2D-Echo-CD in patients with CKD. One hundred and twenty patients with clinical evidence of CKD were enrolled for the present study. The 120 patients were stratified into three stages based eGFR. Significant correlation of serum PTH with ejection fraction were observed in group 3 (P=<0.0001) than groups 1&2 (P=0.2621; P=0.0024 respectively). Abnormal high PTH >250 pg/ml significantly correlates with low EF and significant LVH. There is a role for high PTH in the development of the LVH as well as LV ejection fraction in CKD patients.